2008 58th Electronic Components and Technology Conference 2008
DOI: 10.1109/ectc.2008.4550084
|View full text |Cite
|
Sign up to set email alerts
|

A new method for equivalent acceleration of JEDEC moisture sensitivity levels

Abstract: In order to devise an equivalent accelerated moisture sensitivity test, the JEDEC specification J-STD-020C has recommended an accelerated preconditioning time of 40hrs exposure under 60°C/60%RH, which is considered equivalent to the standard moisture sensitivity level 3 (MSL-3) of 216hrs soak time under 30°C/60%RH. However, the existing methodology for the accelerated moisture sensitivity test was developed based on the equivalency of local moisture concentration at the interest of location for leaded packages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, techniques for in-situ measurement of moisture concentration within electronic packages do not exist due to the small length scales. Furthermore, the comparison of the weight gain of IC packages may not correlate with a moisture concentration inside the IC packages [2][3][4]. Also, Kitano et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, techniques for in-situ measurement of moisture concentration within electronic packages do not exist due to the small length scales. Furthermore, the comparison of the weight gain of IC packages may not correlate with a moisture concentration inside the IC packages [2][3][4]. Also, Kitano et al.…”
Section: Introductionmentioning
confidence: 99%
“…It implies the accelerated equivalent test conditions required to be updated more frequently than ever. However, the weight gain measurements require the long test times (192 or 168 hours) and it also has been reported that the comparison of the weight gain of IC packages may not correlate with a moisture concentration inside the IC packages [3][4][5]. Kitano et al demonstrated the package cracking is not controlled by the absolute weight gain of packages, but the local moisture concentration at the critical interface [3].…”
Section: Introductionmentioning
confidence: 99%